Nuclear Notes - Weiner, Sarah (Rowman & Littlefield Publishers, 2013)
Nuclear Notes is a biannual publication of the CSIS Project on Nuclear Issues (PONI) featuring innovative thinking by rising experts in the nuclear field. Its goal is to advance the public debate about nuclear weapons strategy, arms control, nonproliferation, disarmament, and other nuclear issues by providing a forum for sharing new analysis and insight. In particular, this publication seeks to provide an opportunity for graduate students and early career professionals to publish ideas emanating from their independent research or that are connected to their unique vantage point as analysts and implementers of nuclear policy.